Compact 150 GHz and 300 GHz Dual-Band On-Chip Antenna for Future Communication and Sensing Applications - Pfahler, Tim; Schür, Jan; Vossiek, Martin (2024 IEEE Wireless and Microwave Technology Conference (WAMICON), 2024)
This paper presents the design and measurement of an on-chip dual-band patch antenna which enables simultaneous radiation in the 110–170 GHz and 220–325 GHz frequency band. In addition to frequency diversity, the feed ports are polarization decoupled, thus minimizing crosstalk. Parasitic mode suppression as part of a patch cavity analysis was used to achieve the functionality of the antenna. The measured −10 dB matching bandwidth is 6.5 GHz in the lower and 15.6 GHz in the upper frequency band, respectively. In particular, the simulated peak antenna gain of 3 dBi at 295 GHz can compensate for the higher path losses at sub-THz frequencies. The unique feature of the proposed antenna, compared to other dual-band antennas, is the ability of λ 0 /2 spacing for phase array applications in both frequency bands due to the geometrical compactness of the antenna.<br
Keywords: Antenna measurements; Wireless communication; Phased arrays; Wireless sensor networks; Patch antennas; Dual band; Microwave antenna arrays; Antennas; array; dual-band; dual-polarization; millimeter wave integrated circuits; on-chip; terahertz